A contingent valuation study on Indonesian farmers’ willingness to accept compensation for poultry - Yakhshilikov, Yorbol; Birol, Ekin; Tiongco, Marites; Narrod, Clare; Friedman, Jed (International Food Policy Research Institute, 2009)
In the absence of market data on the price of poultry before and after the outbreak of highly pathogenic avian influenza (HPAI), one method of capturing the costs of HPAI on farmers’ income is the use of non-market valuation techniques, such as the contingent valuation (CV) method (Whitehead 2006). This brief presents the results of a CV study that aimed at capturing farmers’ willingness to accept (WTA) compensation for birds with three different health statuses due to an HPAI outbreak—1) healthy, 2) risky, or 3) sick. The differences among farmers’ willingness to accept compensation for these three types of birds could indicate the extent of the economic costs that may be borne by farmers in the case of an HPAI outbreak. Moreover, the WTA compensation levels could be used to inform the design of efficient, effective, and equitable compensation schemes. This study also investigated that the impact of farmers’ knowledge, attitudes, and perceptions (KAP) of HPAI as well as their poultry-production and household-level characteristics on their WTA compensation (i.e., the HPAI costs that they would bear).